Hindustan Gum, Jodhpur - Rana, R.; Raghuram, G. (London : Indian Institute of Management, Ahmedabad, 2017)
Hindustan Gum is an agro-processor in Jodhpur, Rajasthan. It is primarily in the business of processing guar gum. Demand and prices have become more volatile due to the need for guar gum in the new and growing shale gas fracking, primarily in the US. Hindustan Gum has been trying to respond to this by considering options for raw material supply assurance including contract farming for guar seed sourcing.
Originally Published In Rana, R., Raghuram, G., & Nachiappan, G. (2017). Hindustan Gum, Jodhpur. CMA0818. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Guar gum industry -- India -- Jodhpur -- Case studies; Industrial management -- India -- Jodhpur -- Decision making -- Case studies